How can the integrity of occupational and environmental health research be maintained in the presence of conflicting interests? - Xaver Baur; Colin L. Soskolne; Lisa A. Bero (BMC, 2019)
Abstract Background The sciences, and especially the research subspecialties of occupational and environmental health, are being misused. The misuse serves to interfere with the advancement of policies that depend on rational evidence needed for policies to protect public health. Methods We selectively surveyed the independent scientific literature. In addition, the efforts of respected international professional organizations of scientists whose focus is on maintaining and improving public health have been considered. This commentary is unique in assembling not only the factual basis for sounding alarms about significant bias in occupational and environmental health research, but also about the manipulative mechanisms used, and, in turn, the methods needed to keep science honest. Results Scientific integrity is based on the principle that research is conducted as objectively as possible; it cannot be compromised by special interests whose primary goals are neither to seek truth nor to protect human health. Evidence demonstrates a significant risk of bias in research reports sponsored by financial interests. Practices of corporate malfeasance include the orchestrated contamination of editorial boards of peer-reviewed scientific journals with industry apologists; interference with activities of national regulatory bodies and international review panels engaged in safeguarding occupational and public health; constructing roadblocks by capitalizing on uncertainty to undermine scientific consensus for much-needed government regulation of carcinogenic, endocrine-disrupting and/or immunotoxic agents; promoting "causation" criteria that lack foundation and effectively block workers' access to legal remedies for harms from occupational exposures resulting in morbidity and premature mortality; and, violating standards of professional conduct by seducing reputable scientists with financial incentives that make them beholden to corporate agendas. Conclusions Well-orchestrated assaults on science continue unabated and must now be met head-on. Success could be achieved by promoting and protecting the integrity of research. Furthermore, avoiding influence by conflicted corporate affiliates in occupational and public health regulations is needed. Identifying, managing and, ideally, eliminating corporate influence on science and science policy are needed to protect research integrity. Protecting the public's health, preventing disease, and promoting well-being must be the unambiguous goals of research in occupational and environmental health.